Equivariant algebraic topology applied to some problems in topological combinatorics (2016)
In this thesis we present several results on geometric combinatorics whose solution can be achieved by means of results and tools from algebraic topology. The combinatorial problems are related to known problems as the topological Borsuk problem, equilateral sets in metric spaces, Tverberg type problems, evasiveness of graph properties, etc. Among the results and tools used in the solutions of these problems we find theorems of Borsuk-Ulam and Dold, theorems of Smith and Oliver, group cohomology, cohomology theories, numerical and cohomological index theories